Gambaran Status Nutrisi Pada Pasien dengan Kehilangan Gigi Sebagian Sesuai Klasifikasi Kennedy :Kajian Pada RSGM FKG Usakti (Penelitian) - Jessica Amanda Putri; Indy Labaron (Jurnal Kedokteran Gigi Terpadu, 2020)
Introduction: Tooth loss results in a decrease of the masticatory function which can influence food intake so it is not only affects the oral health but also have an impact on the general health. Objective: The purpose of this study was to explore the nutritional status among patients with partial edentulism according to Kennedy’s classification at Dental and Oral Hospital, Faculty of Dentistry Trisakti University. Materials and methods: This was a descriptive observational study using cross-sectional approach. The data was collected using questionnaire that had been tested for validity and reliability, then examining the oral cavity to determine the partial edentulism pattern based on Kennedy’s classification, and measure the body weight and height to determine the BMI. Results: There were 50 respondents who met the inclusion criteria with an average age of 58.46 years and average BMI of 24.97 kg/m2. In this study it was found that Kennedy’s class III was most commonly encountered in maxillary arch (42%) and class I in mandibular arch (26%). Patients with Kennedy class I and class II cases tend to have moderate nutritional status, whereas patients with class III dan class IV cases tend to have good nutritional status. Conclusions: Patients with Kennedy class III and class IV cases tend to have better nutritional status than patients with class I and class II cases. This is because the number and distribution of teeth also influence nutritional status and body mass index.